UPAYA MENINGKATKAN KETERAMPILAN MEMBACA MELALUI STRATEGI DIRECTED READING THINKING ACTIVITY PADA SISWA KELAS IV SD NEGERI NIRMALA - Farida Salsabila; Deri Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Reading is one of the four crucial language skills. Students' reading proficiency serves as a benchmark for learning. The low reading skills found in grade IV students of SD N Nirmala required action. The purpose of this study was to improve the reading skills of grade IV students of SD N Nirmala with the learning strategy of Directed Reading Thinking Activity. Classroom Action Research is used in research planning. The results of this study showed that in the pre-cycle the value of students' reading skills was 58% complete KKM, then action was taken using the DRTA strategy and in cycle I experienced an increase in KKM completeness of 67%, cycle II 83% and cycle III 83%. From the obtained results, it can be concluded that the DRTA strategy is capable of improving the reading skills of fourth-grade students at SD N Nirmala.